Prevalence and characteristics of starvation‐related malnutrition in a mid‐Atlantic healthcare system: A cohort study. Issue 2 (6th May 2021) - Smith, Luke O.; Vest, Michael T.; Rovner, Alisha J.; Shapero, Mary; Suminski, Richard R.; Trabulsi, Jillian C.; Earthman, Carrie P.
Abstract: Background: Malnutrition in the hospital negatively impacts outcomes, including readmissions, mortality, and cost. Starvation‐related malnutrition (SRM) is a state of chronic undernutrition with little to no inflammation. Research on SRM within the hospital setting is lacking. Our objective was to determine the prevalence and characteristics of malnutrition within the hospital, focusing on characteristics associated with readmissions in those with SRM. Methods: We conducted a retrospective cohort study analyzing characteristics of adult in patients with acute disease–related malnutrition (ADM) and chronic disease–related malnutrition (CDM) compared with patients with SRM. Prevalence of all malnutrition types was calculated as the total number of malnourished patients divided by the total number of hospital discharges. Analysis of variance with Tukey post hoc analysis was performed to determine differences between characteristics of patients with SRM and other forms of malnutrition. Results: Total prevalence of malnutrition was 2.8%. Of malnourished patients, 17.6%, 79.9%, and 2.5% had ADM, CDM, and SRM, respectively. Patients with SRM had lower body mass index (BMI) ( P < .001) and higher rates of readmission ( P = 0.046), infectious disease ( P < .001), psychiatric disease ( P < .001), and substance abuse ( P < .001) than patients with ADM or CDM. Readmitted patients with SRM had lower BMI and higher rates of infection and drug abuse than those without readmission. Conclusion: The high incidence of comorbid substance abuse and mental illness in patients with SRM provide important targets for treatment that might reduce readmission and improve outcomes.